Pemecahan Masalah Matematis Kontekstual Open-Ended Ditinjau dari Self-Efficacy Siswa SMP - Moch. Alfian Nur Fadhila; Ika Kurniasari (MATHEdunesa, 2023)
Mathematical problem solving is student process in solving mathematical problems based on the steps of understanding the problem, devising a plan, carrying out the plan and looking back. The problems can be in the form of contextual open-ended problems. Students’s mathematical problem solving can vary based on the level of student’s self-efficacy. The aim of this research is to describe the contextual open-ended mathematical problem solving in junior high school students with high self-efficacy and low self-efficacy. The type of this research uses descriptive qualitative which was carried out in one of junior high school in Surabaya city, year 2022/2023. Data collection techniques consist of questionnaires, tests and interviews. The chosen subject is one of high self-efficacy student and low self-efficacy student with equivalent mathematical abilities. Data analysis techniques consist of data condensation, data display and verifying based on Polya problem solving steps. The results show at the understanding the problem step, high self-efficacy students are better at determining the known and unknown than low self-efficacy students. Even so, both restate the problem in detail and explain the conditions of data adequacy clearly. At the devising a plan step, high self-efficacy student has initial experience, whereas low self-efficacy student hasn’t. High self-efficacy student devising and explains more plans than low self-efficacy student. At the step of carrying out the plan, both carry out and explain the steps according to the plan. However, high self-efficacy student use more strategies than low self-efficacy student. At the looking back step, high self-efficacy student crosscheck her solutions, stating her conclusions and mention examples of other problems that can be solved in a similar way. Meanwhile, low self-efficacy student just write and explain conclusions inappropriately.